1994
DOI: 10.21273/jashs.119.2.175
|View full text |Cite
|
Sign up to set email alerts
|

Potato Tuber Yield, Mineral Concentration, and Quality after Calcium Fertilization

Abstract: In a 3-year study on a fine sandy loam soil, `Atlantic' (1989), `Frontier' (1990-91), and `Russet Burbank' (1989-91) potato (Solanum tuberosum L.) response to rate and time of Ca fertilization was evaluated. Calcium was applied preplant at 0, 90, 180, and 270 kg·ha-1 as CaSO4 and side-dressed at 0, 34, and 68 kg·ha-1 as Ca(NO3)2, with treatments combined in a complete fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 16 publications
5
23
1
Order By: Relevance
“…Yield was not affected by addition of Ca in this study, regardless of location–year. A similar lack of yield response to additional Ca application has been reported by others (Clough, 1994; Kleinhenz et al, 1999; Silva et al, 1991).…”
Section: Resultssupporting
confidence: 88%
“…Yield was not affected by addition of Ca in this study, regardless of location–year. A similar lack of yield response to additional Ca application has been reported by others (Clough, 1994; Kleinhenz et al, 1999; Silva et al, 1991).…”
Section: Resultssupporting
confidence: 88%
“…However, their experiments showed that supplementation with gypsum (CaSO 4 ) as a source of Ca was not an effective means of increasing tuber Ca, at least at their Michigan test site, leading them to hypothesize that environmental conditions played a more important role in Ca uptake than Ca levels in the soil. In contrast, the experiments of Clough (1994) showed that preplant gypsum addition had a statistically significant effect on reducing IHN severity in Atlantic, and incidence decreased linearly as gypsum preplant rates were increased. Atlantic also displayed reduced IHN incidence with a side-dress application of CaNO 3 .…”
Section: Soil Type and Calcium Level In The Soilmentioning
confidence: 79%
“…These recommendations, as noted earlier, are for the above ground plant growth. Similarly, improvement in tuber quality by in-season application has been reported in sandy loam soils in Oregon (Clough 1994) and fine sandy soils in Florida (Locascio et al 1992).…”
Section: Introductionmentioning
confidence: 56%